Diversity and Density of Mollusca (Gastropoda and Bivalvia) Population in the Euphrates River at Al-Nasiriyah, Southern Iraq - A. Ali Al-Yacoub, G.; Najim , Sh. A.; Al-Khazali , A. M. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2022)
The current study was conducted in one of the most important water sources in Iraq, the Euphrates river to evaluate the diversity and density of Gastropoda and Bivalvia by using appropriate biodiversity indices. The samples were taken monthly from the river sediments, during the period from 1 July 2018 to 1 June 2019 from 3 stations, the distance between the first and second stations is 5 km and the second and third station is 7 km. The results showed the presence of 9 species, 7 of them belong to the Gastropoda and 2 belong to the Bivalvia. The total number of Mollusca was 2675 ind/m2. The species Melanoides tuberculata (Muller 1774) showed more relative abundance in the Euphrates River during the study period. The highest value for richness was recorded in March at station 3, while the Shannon Wiener diversity index, the results showed that the highest values ​​were in April and May for all sites, and the highest value for eveness was recorded in January at Station 3, while the highest value for dominance was during October at station 3. Moreover, the current study included the monthly measurement of five environmental factors: water temperature, pH, salinity, dissolved oxygen, and organic matter.